The Nexus between CDS Premiums and Exchange Rates: Evidence from BRICS Countries and Türkiye - Fatih Güzel; Yüksel İltaş (Ekonomi, Politika & Finans Araştırmaları Dergisi)
This study investigates the long-term relationship between Credit Default Swap (CDS) premiums and exchange rates among the BRICS-T countries (Brazil, Russia, India, China, South Africa, and Turkey) known for their significant impacts on both regional and global dynamics, advanced industrialization, rapid economic growth, and considerable profit potential. Utilizing the RALS-LM unit root test and the RALS-EG cointegration test, and Hacker and Hatemi-J bootstrap causality test, this research circumvents the limitations commonly associated with traditional econometric approaches. A comprehensive and up-to-date dataset, reflecting intensive global and regional movements, was employed, consisting of daily data from January 2020 to June 2024. The findings indicate a long-term relationship between CDS premiums and exchange rates in all countries except Turkey. As the relationship is positive, it can be interpreted that an increase in the exchange rate will increase the CDS premium of countries. In terms of causality, strong evidence that the CDS premium is the cause of the exchange rate is only valid for Turkey. For Brazil, Russia, China and South Africa, we find that the exchange rate is the cause of the CDS premium. As a result, it is concluded that exchange rate movements may affect CDS premiums in these countries.